Revisão taxonômica do gênero Paracanthon Balthasar, 1938 (Coleoptera : Scarabaeidae : Scarabaeinae) - Pacheco, Thaynara Lara (2017)
As presently understood, the genus Paracanthon Balthasar, 1938 includes four nominal species of dung beetles occurring in the Atlantic Forest of northeast, southeastern and south Brazil, as well as in Misiones, Argentina. This taxonomic revision detects the existence of 12 undescribed Paracanthon species. We propose the allocation of P. pereirai in the synonymy of P. rosinae. In addition, we present new data on the morphology of hindwings and male genitalia, addad by an artificial key for practical identification of species. Paracanthon is restricted to the Atlantic domain, and we briefly discuss the possible processes that might have led to the diversification of the lineages recognized herein.